Self Control and Peer Support Reduce Academic Procrastination Levels: Pengendalian Diri dan Dukungan Teman Sebaya Mengurangi Tingkat Penundaan Akademik - Neneng Amelia Ningsih; Eko Hardi Ansyah (Academia Open, 2025)
General Background: Academic procrastination is a common behavioral problem among students characterized by delaying task initiation and completion, which may hinder learning development and academic performance. Specific Background: Internal psychological regulation, such as self-control, and external environmental factors, including peer social support, are recognized as determinants associated with academic procrastination among adolescents in school settings. Knowledge Gap: Previous studies generally examined either self-control or peer social support in relation to academic procrastination, while empirical investigations simultaneously examining these variables within a single analytical framework remain limited. Aims: This study aimed to examine the relationship between self-control and peer social support with academic procrastination among students at SMA Ma’arif NU Pandaan. Results: Using an inferential quantitative design with 218 participants selected through accidental sampling, data were collected using three measurement scales consisting of 28 self-control items (reliability 0.919), 22 peer social support items (reliability 0.729), and 43 academic procrastination items (reliability 0.994), analyzed through multiple linear regression using JASP. The findings indicated a significant simultaneous relationship between self-control and peer social support with academic procrastination (F = 16.239; p < 0.001), with self-control contributing 5% and peer social support contributing 8.1% to academic procrastination variance, while both variables explained 13.1% of total variance. Regression analysis revealed that increased self-control and peer social support were associated with decreased academic procrastination scores. Novelty: This study integrates internal and external psychosocial variables simultaneously to examine academic procrastination among senior high school students. Implications: The results highlight the relevance of strengthening self-regulation capacity and supportive peer environments to address procrastination behavior in educational contexts. Keywords: Self Control, Peer Social Support, Academic Procrastination, Adolescents, Multiple Regression